1992
DOI: 10.1182/blood.v79.10.2540.2540
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter randomized study comparing cyclosporine-A alone and antithymocyte globulin with prednisone for treatment of severe aplastic anemia

Abstract: We report the results of a randomized multicenter study comparing the efficacy of antithymocyte globulin (ATG) with that of cyclosporin A (CsA) as first-line therapy for severe aplastic anemia (SAA). Patients were randomized to receive ATG and prednisone (PDN) or CsA; hematologic response and toxicity were compared. At 3-month evaluation, patients who had no or minimal response received the alternative therapy to assess the value of a sequential immunosuppressive therapy for treatment of severe aplastic anemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 35 publications
1
21
1
Order By: Relevance
“…Comparisons of our findings with reports in the literature indicate that many patients with AA in Iran who did not receive ATG therapeutic regimens did relatively well. Gluckman et al in a randomized controlled study found better result with CsA comparing to ATG but skill in treatment delivery and infection control gave superiority to ATG in later years [ 15 ]. Our results showed no influence from ATG infusion in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons of our findings with reports in the literature indicate that many patients with AA in Iran who did not receive ATG therapeutic regimens did relatively well. Gluckman et al in a randomized controlled study found better result with CsA comparing to ATG but skill in treatment delivery and infection control gave superiority to ATG in later years [ 15 ]. Our results showed no influence from ATG infusion in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…Since this is likely a selection of patients and is not representative of the entire patient population, the role of ELT in the first-line setting could not be clarified in our cohort. The response rate of 46.7% in patients with low intensity ELT treatment in the first-line setting is certainly meaningful, but not above the range expected, e.g., with CYA alone [26].…”
Section: Discussionmentioning
confidence: 79%
“…However, there is an associated risk of thrombocytopenia with these drugs; therefore, platelet transfusion should be administerd. Furthermore, the use of cyclosporine was found to have results comparable to ATG in pregnant mothers 11 . A few reports demonstrated the safe use of cyclosporine in pregnant mothers who underwent organ transplant 12 .…”
Section: Discussionmentioning
confidence: 94%